Daily Consumption of Oregon Hazelnuts Affects α-Tocopherol Status in Healthy Older Adults: A Pre-Post Intervention Study. Issue 12 (5th December 2018) - Michels, Alexander J; Leonard, Scott W; Uesugi, Sandra L; Bobe, Gerd; Frei, Balz; Traber, Maret G
ABSTRACT: Background: Inadequate vitamin E and magnesium intakes are of concern for older adults owing to the associated incidence of age-related diseases. Objective: This study was designed to determine the extent to which a 16-wk intervention with hazelnuts alters vitamin E and magnesium status in a group of older men and women, and used a pre-post intervention design without a control group to adjust for temporal changes. Methods: Participants ( n  = 32 including 22 women; mean ± SD age: 63 ± 6 y) consumed hazelnuts (∼57 g/d) for 16 wk. Blood and urine samples and anthropomorphic measures were taken at the start and end of the intervention to determine plasma concentrations of α-tocopherol and serum concentrations of magnesium, lipids, glucose, insulin, and high-sensitivity C-reactive protein along with urinary vitamin E metabolites; several other micronutrients were measured by a lymphocyte proliferation assay. There were 3 primary endpoints, calculated as the mean changes in measurements between baseline and the end of the 16-wk intervention for 1 ) plasma α-tocopherol, 2 ) urinary α-carboxyethyl hydroxychromanol (α-CEHC; an α-tocopherol metabolite), and 3 ) serum magnesium. Results: Hazelnut consumption increased concentrations of the urinary α-tocopherol metabolite α-CEHC (mean ± SD: 0.84 ± 0.45 to 1.14 ± 0.50 µmol/g creatinine; P =  0.0006). In addition, hazelnut consumption increased serum concentrations of magnesium (+2.1%, P =  0.05), decreased concentrations of fasting glucose (−3.4%, P =  0.03) and LDL cholesterol (−6.0%, P =  0.02), and decreased total:HDL cholesterol ratios (−4.5%, P =  0.009). No significant changes were observed in blood pressure, lymphocyte proliferation assays, and serum concentrations of insulin, high-sensitivity C-reactive protein, triglyceride, α-tocopherol, or HDL cholesterol. Conclusions: Consuming hazelnuts improves a biomarker of vitamin E status in older adults. Vitamin E is a shortfall micronutrient, as identified by the Dietary Guidelines for Americans 2015–2020, which frequently is consumed at levels less than the Estimated Average Requirement of 12 mg/d; thus, hazelnuts should be considered as part of a healthy dietary pattern. This trial was registered at clinicaltrials.gov as NCT03485989.